Prevalence of Mycobacterium lentiflavum in cystic fibrosis patients, France. Issue 1 (December 2015) - Phelippeau, Michael; Dubus, Jean-Christophe; Reynaud-Gaubert, Martine; Gomez, Carine; Stremler le Bel, Nathalie; Bedotto, Marielle; Prudent, Elsa; Drancourt, Michel
Abstract Background Mycobacterium lentiflavum is rarely isolated in respiratory tract samples from cystic fibrosis patients. We herein describe an unusually high prevalence ofM. lentiflavum in such patients. Methods M. lentiflavum, isolated from the respiratory tract of cystic fibrosis patients, was identified using bothrpoB partial sequencing and detected directly in the sputum by using real-time PCR targeting thesmpB gene. Results M. lentiflavum emerged as the third most prevalent nontuberculous mycobacterial species isolated in cystic fibrosis patients in Marseille, France. Six such patients were all male, and two of them may have fulfilled the American Thoracic Society clinical and microbiological criteria forM. lentiflavum potential lung infection. Conclusions M. lentiflavum was the third most common mycobacteria isolated in cystic fibrosis patients, particularly in six male patients.M. lentiflavum outbreaks are emerging particularly in cystic fibrosis patients.